Democratic Republic of the Congo : Request for the Rapid-Access Component of the Exogenous Shocks Facility and Report on the 2008 Staff Monitored Program. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses a request from Congo for the Rapid-Access Component of the Exogenous Shocks Facility. Performance on the 2008 staff-monitored program was mixed, complicated by the effects of the exogenous shock. Although weaknesses remain, the authorities strengthened public financial management, particularly with regard to urgent government expenditure. They also made progress in addressing IMF staff's concerns about the debt sustainability implications of the Sino-Congolese mining and infrastructure cooperation agreement. The authorities are committed to implementing appropriate adjustment policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet